Using expert consensus to develop a simulation course for faculty members. (February 2015) - Kinnear, John; Smith, Barry; Akram, Majid; Wilson, Nick; Simpson, Emily
Summary Background Effective learning from simulation‐based training depends on expert facilitation by skilled faculty members, but there are few guidelines upon which to base simulation development. A collaborative approach was taken in the East of England to determine the agreed content of such a course. Methods A modified Delphi method was used to determine consensus amongst the simulation‐provider leads in the East of England on what should be the essential elements of a training course for faculty members. A questionnaire designed by a steering group was circulated to the consensus group, and their responses were used to modify subsequent questionnaires. There was enough agreement after two rounds not to require a third round. Results After two rounds there was high level of agreement that the educational content should include scenario design, creating a supportive learning environment, structured debriefing formats, human factors, educational feedback and communication. There was also agreement on preferred teaching methods, minimum qualification and continuing development for faculty members. There was moderate agreement on the prior experience required of faculty members, and no agreement on the costs of courses. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Effective learning from simulation‐based training depends upon expert facilitation by skilled faculty members </boxed-text> Discussion By using a consensus method to determine the content and format of a simulation development course designed for faculty members, there is agreement in the East of England on what constitutes an educationally sound programme. This should provide assurance to both simulation providers and commissioners of education that despite the absence of guidelines, there is an agreed practice standard for simulation‐based training in the region.